A gazdasági stabilizációs diskurzus - a konszolidáció diskurzusa - Csigó, Péter (Szociológiai Szemle, 2024)
The completion of systemic change, that is consolidation has become one of the most popular topics of public thinking and of social sciences. Struggles along consolidation have also appeared on the level of political discourses. Primarily in the discourse on economic stabilisation, which was the most significant discourse of the period of the Horn-government. Partly because it was constantly present and that too in an outstanding quantity, and partly because it also had a focal role in the self-representation of the political actors. In my paper I wish to present what kind of linguistic efforts were made with the aim of consolidating systemic change during the course of the discourse about economic stabilisation, and what efforts at de-consolidation, that is challenging the direction of systemic change, appeared in public debates on the economic policy of stabilisation. I conduct the analysis with the help of a specific method of discourse analysis (“structural discourse analysis”). My objective is to describe the structure o f the field o f discourse organised around the issue of stabilisation. Thus the alternative forms of knowledge appearing in the discourse are presented, together with 1. what kind of statements and topical groups of statements they consist of, 2. what kind of unpronounced suppositions they carry, 3. what actors produce and assert them 4. by the help of what strategies